'n Eksegeties-teologiese interpretasie van Habakuk 3 - S. D. Snyman (Acta Theologica)
In this article Habakkuk 3 is subjected to an exegetical-theological interpretation. After a preliminary translation serving as a working translation to clear obscurities in the Afrikaans version of  Habakkuk 3, attention is paid to the demarcation of the unit, text critical matters, a structural analysis of the text (revealing an inclusio), genre (mixture of Gattungen), setting in life, tradition material (Sinai, Exodus, Conquest and Creation) and redactional issues. Habakkuk 3 provides a vision of Yahweh amidst the troubling times of the pending Babylonian exile. As He once revealed Himself in a majestic theophany, He will do so again. In the mean time believers must patiently await His intervention which will surely happen in due course.